The Role of Health Status and Social Capital in Cancer Mortality: - Geir Godager; Eline Aas; Christian B. H. Thorjussen (University of Oslo, 2023)
Abstract: Cancer mortality has been shown to be associated with social- and human capital. Several channels have been suggested, such as early detection, better compliance to treatment and better health prior to diagnosis. In this paper we study how health status and social capital jointly affect cancer mortality and cancer severity at the time of diagnosis. The analyses are based on study sample of individuals with cancer diagnosis. Our merged dataset contain information on cancer diagnosis and death from the Cancer Registry of Norway and health status, social capital and other individual level data from several national health surveys measured before the time of diagnosis. Health status and social capital are treated as unobserved latent variables, and we apply generalized structural equation modelling framework to estimate conditional statistical associations of social capital and individual health on cancer severity and mortality. We find that health has negative, and statistically significant effect, on cancer mortality, while we cannot conclude on the association between health and cancer severity (metastasis yes/no). We cannot conclude that cancer mortality and the probability of cancer metastasis is associated nor disassociated with social capital. Our results add nuance to prior studies, which frequently report a significant association between social capital and cancer mortality.